Stereotypy dotyczące płci a przemoc wobec kobiet w dorobku prawnomiędzynarodowym. Od identyfikacji do kształtowania instrumentów prawnych: [Gender Stereotyping and Violence against Women under International Law. From Recognition to Development of the Legal Instruments] (Studia Prawnicze / The Legal Studies, 2016)
Celem artykułu jest wykazanie, że pomimo dużej ogólności regulacji dotyczących expressis verbis relacji pomiędzy stereotypami dotyczącymi płci a dyskryminacją, dostrzeżenie tej kwestii na gruncie prawa międzynarodowego doprowadziło do ukształtowania konkretnych instrumentów w materii przeciwdziałania przemocy wobec kobiet. Kluczowe znaczenie należy przypisać procesowi identyfikacji stereotypów i uprzedzeń, które negatywnie wpływają na sytuację kobiet będących ofiarami przemocy. Rozpoznanie przekonań stojących za pewnymi postawami organów ścigania i wymiaru sprawiedliwości pozwoliło na zdefiniowanie instrumentów prawnych mających niwelować ich skutki i przeciwdziałać dalszej stereotypizacji zjawiska przemocy wobec kobiet. The obligation to counteract gender stereotypes resulting in discrimination against women, including violence against women, was anchored in international law by the Convention on the Elimination of All Forms of Discrimination against Women of 1979. The article aims to demonstrate that although the relevant regulations are of a very general nature, the recognition of this issue in international law allowed the particular instruments which may counteract violence against women to be developed. The international output in this matter may be divided into two key stages – a stage of recognition of particular stereotypes in the case law of international human rights bodies and a stage of development of legal instruments aimed to counteract gender stereotyping. Thus the article attempts to link the stereotypes identified in the practice of the Committee on Elimination of All Forms of Discrimination against Women and the European Court of Human Rights with instruments developed in the most comprehensive international treaty concerning the violence against women, i.e. the Council of Europe Convention on preventing and combating violence against women and domestic violence of 2011.